2007
DOI: 10.1074/jbc.m610745200
|View full text |Cite
|
Sign up to set email alerts
|

Three Mammalian Lipins Act as Phosphatidate Phosphatases with Distinct Tissue Expression Patterns

Abstract: We previously identified mutations in the Lpin1 gene, encoding lipin-1, as the underlying cause of lipodystrophy in the fatty liver dystrophy (fld) mutant mouse. Lipin-1 is normally expressed at high levels in adipose tissue and skeletal muscle, and deficiency in the fld mouse causes impaired adipose tissue development, insulin resistance, and altered energy expenditure. We also identified two additional lipin protein family members of unknown function, lipin-2 and lipin-3. Han et al. Triacylglycerol (TAG)3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
460
4
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(500 citation statements)
references
References 32 publications
14
460
4
16
Order By: Relevance
“…LPIN3 is a human phosphatidate phosphatase, which has phosphatidate phosphatase type-1 (PAP1) activity and has a key role in glycerolipid metabolism (Donkor et al, 2007;Reue and Brindley, 2008). In the present study, we have identified a cell-penetrating amino acid sequence from LPIN3 and proved its delivery efficiency in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…LPIN3 is a human phosphatidate phosphatase, which has phosphatidate phosphatase type-1 (PAP1) activity and has a key role in glycerolipid metabolism (Donkor et al, 2007;Reue and Brindley, 2008). In the present study, we have identified a cell-penetrating amino acid sequence from LPIN3 and proved its delivery efficiency in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 78%
“…LPINs are phosphatidate phosphatases that have multiple roles in the regulation of lipid metabolism and cell signaling (Donkor et al, 2007;Reue and Brindley, 2008). Most previous studies about LPINs involved lipid biosynthesis and its related roles in adipose tissue or, more recently, in macrophages (Valdearcos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…LPIN1 is a PAP1 enzyme, which is required in the de novo biosynthesis of TG, phosphatidylcholine and phosphatidylethanolamine (Donkor et al, 2007). Here chicken Lpin1 ORF was cloned and its conservative elements were revealed.…”
Section: Discussionmentioning
confidence: 99%
“…First, LPIN1, as well as the related LPIN2 and LPIN3 proteins, acts as Mg 21 -dependent phosphatidate phosphatase type-1 (PAP1) enzymes, which catalyze a key step in the synthesis of glycerolipids (Han et al, 2006;Donkor et al, 2007;Harris et al, 2007). Second, Lpin1 can also act as a transcriptional coactivator.…”
Section: Introductionmentioning
confidence: 99%
“…Three lipin family genes including lipin-1, lipin-2, and lipin-3 have been found, and exhibit distinct tissue-specific expression patterns [2]. In adipocytes, lipin-1 is expressed at high levels, whereas lipin-2 is presented at low levels in mice [2].…”
Section: Introductionmentioning
confidence: 99%